1993
DOI: 10.3109/02770909309066376
|View full text |Cite
|
Sign up to set email alerts
|

Early Wheezing and Breast Feeding

Abstract: There is uncertainty as to whether breast feeding protects against subsequent illnesses; it has been suggested that breast feeding may have some protective effects on the severity of long-term outcome of bronchiolitis and in reducing morbidity. We have assessed the effects of breast feeding in 266 patients and 199 controls, all patients were early wheezers (i.e., under 2 years old). Between these groups we found differences in socioeconomic, environmental, and atopic conditions, but there were no significant d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1994
1994
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 16 publications
0
4
0
Order By: Relevance
“…Even if mothers of babies at risk of developing allergy stick to a strict avoidance diet during pregnancy there is no protective effe~t..~.~~ A similar avoidance diet during lactation does, however, decrease the incidence of atopic dermatiti~.~~.~' In a recent study, exclusive breast feeding for 6 months was regarded as a useful prophylactic measure against allergy.48 Early wheezing may also be decreased by breast feeding. 49 Interestingly, the more antibodies there are to cow's milk in the mother's milk, the less the risk of developing cow's milk a l l e r g~.~~3 '…”
Section: Breast Feeding and Allergymentioning
confidence: 99%
“…Even if mothers of babies at risk of developing allergy stick to a strict avoidance diet during pregnancy there is no protective effe~t..~.~~ A similar avoidance diet during lactation does, however, decrease the incidence of atopic dermatiti~.~~.~' In a recent study, exclusive breast feeding for 6 months was regarded as a useful prophylactic measure against allergy.48 Early wheezing may also be decreased by breast feeding. 49 Interestingly, the more antibodies there are to cow's milk in the mother's milk, the less the risk of developing cow's milk a l l e r g~.~~3 '…”
Section: Breast Feeding and Allergymentioning
confidence: 99%
“…However, breast-fed infants have a lower morbidity and mortality than formula-fed infants. Studies have demonstrated significant infant protection against diarrhea, respiratory tract infections, otitis media, bacteremia, bacterial meningitis, botulism, urinary tract infections, necrotizing enterocolitis, and other diseases while the infant is receiving breast milk (1)(2)(3)(4)(5). There is also good evidence of continued protection against these medical conditions for years after breast-feeding has terminated (1, 6 -11).…”
mentioning
confidence: 97%
“…10,11 Wheezing illness has been shown to be decreased for up to 6 to 7 years after the termination of breastfeeding compared with nonbreastfeeding. [12][13][14] Wilson et al 14 also demonstrated that children who had been exclusively breastfed for 15 weeks remained better protected against respiratory tract infections for ∼7 years compared with those not breastfed. Saarinen 15 found that any amount of breastfeeding for 3 to 4 months decreased the risk of developing otitis media up to the age of 3 years, whereas Howie et al 16 found that any breastfeeding for at least 13 weeks was not associated with ear infection but was associated with a significantly lower prevalence of gastrointestinal disease in the first 2 years of life compared with those who were never breastfed or breastfed ,13 weeks.…”
mentioning
confidence: 99%